The Effect of Addition of Andaliman Fruit (Zanthoxylum acanthopodium dc) on Physical Quality and Organoleptic Testing of Buffalo Meat Sausage - Tomy Fihgter Karo karo; Nurzainah Ginting; Fuad Hasan (Jurnal Peternakan Integratif, 2025)
Meat is one of the ingredients that is susceptible to physical damage caused by biochemical activity. Andaliman has biological activities such as antioxidants, anti-inflammatory, and antimicrobial. This study aims to determine the effect of giving Andaliman fruit (Zanthoxylum acanthopodium DC) on the physical quality and organoleptic test of buffalo meat sausages which were carried out in May-June 2025 at the Animal Production Laboratory, Animal Husbandry Study Program, Faculty of Agriculture, Universitas Sumatera Utara. The design used in this study was a Completely Randomized Design with 4 treatments and 5 replications. The treatment consisted of giving Andaliman extract (P0 = 0%; P1 = 0.2%; P2 = 0.4%; P3 = 0.6%). The parameters observed were the physical quality of the sausage, including pH value, percentage of water binding capacity, and percentage of cooking loss as well as organoleptic tests of the sausage. The results of this study indicate that the administration of Andaliman extract (Zanthoxylum acanthopodium DC) gave very significant different results on pH value, water binding capacity and sausage cooking loss. The administration of Andaliman extract (Zanthoxylum acanthopodium DC) gave very significant different results on the color, aroma, texture and taste of sausages. The best treatment results were found in P3, namely with a concentration of 0.6%.